Ethical aspects of donor consent in transplantation - Mahoney, John (Journal of medical ethics, 1975)
Two recent events have caused renewed anxiety concerning the ethics of donor transplantation. The first is the report of the British Transplantation Society and the second is the Bill introduced by Mr Tam Dalyell MP (see page 61 of this issue) in which he seeks to establish by law that unless an individual in his life time has expressly contracted out his organs may after death be used for transplantation. Dr Mahoney in this paper therefore examines from the point of view of ethics some of the personal and social aspects of both proposals.